Reclaiming Evangelism. (July 2016) - Woods, Philip
Abstract: This paper introduces approaches to reclaiming evangelism, noting the challenges and opportunities of our changing global context, and stressing the importance of authentic witness. The author draws on the Council for World Mission's work promoting the development of missional congregations as life‐affirming communities and its statement identifying six conversation threads (the absence of God; secularism; issues of identity; how we affirm life; the sources we use to shape and nurture our faith; and how we overcome fear and violence in our societies and in the world) that need to be developed on Christian witness in a pluralist world.